THE ROLE OF INTIMA-MEDIA-THICKNESS, ANKLE BRACHIAL-INDEX, AND INFLAMMATORY BIOCHEMICAL PARAMETERS FOR STROKE RISK PREDICTION: AN UPDATE SYSTEMATIC REVIEW - Aulia Fajri, Azda; Hartono, Budi; Priscika Putri, Deby; Azhari, Ririn; Merisa L, Bella; Ananda, Astrid; Syarfina, Afdila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Stroke is a leading cause of global mortality and morbidity. The capacity to precisely estimate a person's risk of having a stroke is critical for early intervention and prevention stretegies. Researchers are exploring novel predictors beyond traditional risk factors, such as Intima-Media Thickness (IMT), Ankle-Brachial Index (ABI), and inflammatory biochemical parameters, to accurately predict stroke risk. The aim: This study aims to determine the role of intima-media-thickness, ankle-brachial-index, and inflammatory biochemical parameters for stroke risk prediction. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SAGEPUB, and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 1,004 articles, whereas the results of our search on SAGEPUB brought up 651 articles, and our search on ScienceDirect brought up 4,254 articles. In the end, we compiled 12 papers, 8 of which came from PubMed, 1 of which came from SAGEPUB, and 3 of which came from ScienceDirect. We included twelve research that met the criteria. Conclusion: In conclusion, the findings of our study strongly support that Carotid Intima-Media Thickness (CIMT) and Ankle-Brachial Index (ABI) hold significant promise as predictors of stroke risk. This can be helpful to improve stroke prevention and management strategies. However, further research is warranted to clarify the role of inflammatory biochemical parameters in the context of stroke risk prediction.